As you like it - Shakespeare, William, 1564-1616.; Harrison, G. B. (George Bagshawe), 1894-1991. (Harmondsworth : Penguin, 1994)
As You Like It is considered by many to be one of Shakespeare's greatest comedies, and the heroine, Rosalind, is praised as one of his most inspiring characters and has more lines than any of Shakespeare's female characters. Rosalind, the daughter of a banished duke falls in love with Orlando the disinherited son of one of the duke's friends. When she is banished from the court by her usurping uncle, Duke Frederick, Rosalind switches genders and as Ganymede travels with her loyal cousin Celia and the jester Touchstone to the Forest of Arden, where her father and his friends live in exile. Observations on life and love follow (including love, aging, the natural world, and death) friends are made, and families are reunited. By the play's end Ganymede, once again Rosalind, marries her Orlando. Two other sets of lovers are also wed, one of them Celia and Orlando's mean older brother Oliver . As Oliver becomes a gentler, kinder young man so the Duke conveniently changes his ways and turns to religion and so that the exiled Duke, father of Rosalind, can rule once again.
Keywords: Fathers and daughters -- Drama; Exiles -- Drama; English drama -- Early modern and Elizabethan, 1500-1600.